Bupropion decreases plasma levels of asymmetric dimethylarginine and ameliorates renal injury by modulation of Ddah1, Oatp4c1, Oct2, and Mate1 in rats with adenine-induced chronic renal injury - Huang, Lulu; Xiao, Yun; Han, Xiaoyu; Yu, Yang; Zheng, Chao; Fang, Xiangdong; Li, Qing; Liu, Fanglan; Xia, Chunhua; Zhang, Yongjie; He, Jiake (Frontiers in Pharmacology, 2025)
ObjectiveThe objective of the study was to investigate whether bupropion (BUP) or its circulation metabolites could decrease plasma level of asymmetric dimethylarginine (ADMA) and ameliorate renal injury by modulation of Ddah1, Oatp4c1, Oct2, and Mate1 in rats with adenine-induced chronic renal injury.MethodsThe study initially determined the effect of BUP and its metabolites on cell viability and apoptosis in HK2 cells in the presence and absence of ADMA. Secondly, the study explored whether long-term administration of BUP could reduce the plasma level of ADMA and mitigate renal damage. Thirdly, the expression and activity of Oct2, Ddah1, Mate1 and Oatp4c1 was determined by Western blot and UPLC-MS/MS.ResultsWith 0.5 μmol/L ADMA, hydroxybupropion (HBUP, 100 nmol/L), threo-hydrobupropion (TBUP, 10 nmol/L and 1 μmol/L) reduced N-Acetyl-β-D-glucosidase (NAG) level. At 5 μmol/L ADMA, BUP (1 nmol/L-1 μmol/L), HBUP (1–100 nmol/L), and BUP cocktail enhanced survival. At 50 μmol/L ADMA, HBUP (10 nmol/L and 1 μmol/L), TBUP/erythro-hydrobupropion (EBUP) (10–100 nmol/L), and BUP cocktail stimulated survival. EBUP (1 and 100 nmol/L) lowered LDH. BUP (100 nmol/L) and TBUP (1 μmol/L) decreased NAG. TBUP (10 nmol/L, 1 μmol/L) and EBUP (100 nmol/L) inhibited apoptosis. In adenine-induced chronic renal injury rats, long-term administration of BUP significantly decreased the serum concentration of ADMA and creatinine by 12.78% and 38.85%, respectively, ameliorated interstitial lesions and fibrosis and upregulated Ddah1, Oatp4c1, Oct2, Mate1. BUP increased metformin renal clearance without affecting digoxin disposition.ConclusionBupropion moderately decreases plasma levels of ADMA and ameliorates renal injury by modulation of Ddah1, Oatp4c1, Oct2, and Mate1.